Phylogeny and evolution of apicoplasts and apicomplexan parasites. Issue 3 (June 2015) - Arisue, Nobuko; Hashimoto, Tetsuo
Abstract: The phylum Apicomplexa includes many parasitic genera of medical and veterinary importance including Plasmodium (causative agent of malaria), Toxoplasma (toxoplasmosis), and Babesia (babesiosis). Most of the apicomplexan parasites possess a unique, essential organelle, the apicoplast, which is a plastid without photosynthetic ability. Although the apicoplast is considered to have evolved through secondary endosymbiosis of a red alga into the common ancestral cell of apicomplexans, its evolutionary history has been under debate until recently. The apicoplast has a genome around 30–40 kb in length. Repertoire and arrangement of the apicoplast genome-encoded genes differ among apicomplexan genera, although within the genus Plasmodium these are almost conserved. Genes in the apicoplast genome may be useful markers for Plasmodium phylogeny, because these are single copy (except for the inverted repeat region) and may have more phylogenetic signal than the mitochondrial genome that have been most commonly used for Plasmodium phylogeny. This review describes recent studies concerning the evolutionary origin of the apicoplast, presents evolutionary comparison of the primary structures of apicoplast genomes from apicomplexan parasites, and summarizes recent findings of malaria phylogeny based on apicoplast genome-encoded genes. Graphical abstract: Highlights: The apicoplast has evolved through secondary endosymbiosis of a red alga. The apicoplast has a genome around 30–40 kb. The repertoire and arrangement of the apicoplast genes are different among genera. Genes in the apicoplast genome can be useful markers for phylogeny of Plasmodium .